Electrically switchable metasurface for beam steering using PEDOT polymers. (27th November 2020) - Ratzsch, Juliane; Karst, Julian; Fu, Jinglin; Ubl, Monika; Pohl, Tobias; Sterl, Florian; Malacrida, Claudia; Wieland, Matthias; Reineke, Bernhard; Zentgraf, Thomas; Ludwigs, Sabine; Hentschel, Mario; et al.
Abstract: Switchable and active metasurfaces allow for the realization of beam steering, zoomable metalenses, and dynamic holography. To achieve this goal, one has to combine high-performance metasurfaces with switchable materials that exhibit high refractive index contrast and high switching speeds. In this work, we present an electrochemically switchable metasurface for beam steering where we use the conducting polymer poly(3, 4-ethylenedioxythiophene) as an active material. We show beam diffraction with angles up to 10° and a change of the intensities of the diffracted and primary beams employing an externally applied cyclic voltage between −1 V and +0.5 V. With this unique combination, we realize switching speeds in the range of 1 Hz, and the extension to typical display frequencies in the region of tens of hertz is possible. Our findings have immediate implications for the design and fabrication of future electronically switchable and display nanotechnologies, such as dynamic holograms.